2016
DOI: 10.1088/1009-0630/18/4/05
|View full text |Cite
|
Sign up to set email alerts
|

The Instability of Terahertz Plasma Waves in Two Dimensional Gated and Ungated Quantum Electron Gas

Abstract: The instability of terahertz (THz) plasma waves in two-dimensional (2D) quantum electron gas in a nanometer field effect transistor (FET) with asymmetrical boundary conditions has been investigated. We analyze THz plasma waves of two parts of the 2D quantum electron gas: gated and ungated regions. The results show that the radiation frequency and the increment (radiation power) in 2D ungated quantum electron gas are much higher than that in 2D gated quantum electron gas. The quantum effects always enhance the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…where the K 1 and K 2 can be found from equation (10). Equation ( 14) is a transcendental equation that can be only solved numerically.…”
Section: Plasma Waves Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…where the K 1 and K 2 can be found from equation (10). Equation ( 14) is a transcendental equation that can be only solved numerically.…”
Section: Plasma Waves Instabilitymentioning
confidence: 99%
“…For two-dimensional electron gas (2DEG) in channel of FET, the mean free path of electron-electron collisions is less than both the channel length and the mean free path of collisions with impurities and/or phonons, which causes the electron scattering and the viscosity of plasma [8,9]. Most scientists have concerned about the influence of geometry of device on THz plasma waves [10][11][12][13]. Dyakonov and Shur used a new equation to replace the gradual-channel equation and noted that the instability in ungated FETs was similar to gated FETs with asymmetrical boundary conditions [12].…”
Section: Introductionmentioning
confidence: 99%
“…we obtain 15 This is greater than one, meaning that the amplitude of plasma in an NDC HEMT with the same condition is more than in an ordinary transistor. For a numerical example we use the estimation of references [4,15] as a typical value for  h » » m 0.0018. As an example we consider the data in [1] as For a gate to source DC bias of j = 1 2 0 V, we obtain A HEMT =0.3074, A NDC =0.3974.…”
Section: Dyakonov-shur Instabilitymentioning
confidence: 99%
“…In [15] the gated and ungated region of a two-dimensional quantum electron gas (2DQEG) has been investigated, showing that the radiation frequency and the instability in an ungated 2DQEG are much higher than that in a gated 2DQEG. The quantum effects always enhance the instability and finally he concluded that both gated and ungated parts take part in that process of emission and detection.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the plasma wave is similar to 'shallow water' waves in a ballistic FET. It is indicated that the instability with zero ac voltage at the source and zero ac current at the drain can occurs when the asymmetric boundary conditions are satisfied [2,3]. Most of the previous work demonstrated the THz plasma wave instability in short-channel FET is essential to the realization of practical non-resonant detectors [4][5][6], resonant detectors [7], and the terahertz emitters [8] in the terahertz domain [4].…”
Section: Introductionmentioning
confidence: 99%